Harmonic reduction of a single-phase multilevel inverter using genetic algorithm and particle swarm optimization - Ling, Chin Wan (2016)
Inverter play important role in power system especially with it capability on reducing system size and increase efficient. Recent research trend of power electronics system are focusing on multilevel inverter topic in optimization on voltage output, reduce total harmonics distortion, modulation technique and switching configuration. Standalone application multilevel inverter is high focused due to the rise of renewable energy policy all around the world. Hence, this research emphasis on identify best topology of multilevel inverter and optimize it among the diode-clamped, capacitor clamped and cascaded H-bridge multilevel inverter to be used for standalone application in term of total harmonics distortion and voltage boosting capability. The first part of research that is identify best topology multilevel inverter is applying sinusoidal pulse width modulation technique. The result shown cascade H-bridge give the best output in both total harmonics distortion (9.27%) and fundamental component voltage (240 Vrms). The research proceed with optimization with fundamental switching frequency method that is optimized harmonic stepped waveform modulation method. The selective harmonics elimination calculation have adapt with genetic algorithm and particle swarm optimization in order to speed up the calculation. Both bio-inspired algorithm is compared in term of total harmonic distortion and selected harmonics elimination for both equal and unequal sources. In overall result shown both algorithm have high accuracy in solving the non-linear equation. However, genetic algorithm shown better output quality in term of selected harmonics elimination where overall no exceeding 0.4%. Particle swarm optimization shows strength in finding best total harmonics distortion where in 7-level cascaded H-bridge multilevel inverter (m=0.8) show 6.8% only as compared to genetic algorithm. Simulation for 3-level, 5-level and 7-level for each multilevel inverter at different circumferences had been done in this research. The result draw out a conclusion where the possibility of having a filterless high efficient invert can be achieve.